UPAYA PEMBERDAYAAN UMKM MELALUI SOSIALISASI PEMBUKUAN DAN PEMASARAN DESA SEBAUNG - Hermawan, Dedi Joko; Hakim, Lukman; Elmas, Muhammad Syarif Hidayatullah; Kristiyono, Kristiyono; Syarofah, Alfiatus; Kurniawati, Ajunaida; Agata, Chintya Amelia; Diansyah, Muhammad Rival; Zannah, Fatulil (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
The problem of bookkeeping and marketing is inseparable from the potential of MSMEs in Sebaung Village, Gending District, Probolinggo Regency, which is very large and diverse. Maintaining a business based on financial aspects is one of the problems of MSMEs in Sebaung Village. The implementation of this community service program aims to help MSMEs in Sebaung Village regarding their understanding of simple financial bookkeeping and marketing. The method of implementing this community service begins with conducting socialization of bookkeeping and marketing to MSME actors, village organizations, and residents. The implementation of this socialization was held at the Sebaung village hall. First, this activity began with an explanation of the material on Marketing and continued with material on simple bookkeeping. After that, a question and answer session was held. Then the committee provided assistance to participants regarding digital marketing training and bookkeeping. The socialization of Bookkeeping and Marketing went smoothly and was full of enthusiasm from MSME participants, as evidenced by their communication during questions and answers regarding the material that had been presented and also sharing about the MSME business being run. The result of this service is that MSME actors, village organizations, and residents gain new insights to know how to manage bookkeeping and marketing properly and correctly and reduce the possibilities that cause losses for MSME actors in running their businesses.. Keywords: Socialization, MSMEs, Sebaung